ANTIHYPOXIC PROPERTIES OF THE DRY EXTRACT FROM SERRATULA CENTAUROIDES - V. .. Sviridov; Ya. G. Razuvaeva; L. N. Shantanova (Acta Biomedica Scientifica, 2014)
The influence of the dry extract from Serratula centauroides roots on the resistance to the hemic, hystotoxic and hypercapnic hypoxias was investigated in the experiments on white rats. It was established that the course administration of the remedy in the doses of50,100,150 mg/kg increases the resistance of the experimental animals to hypoxias of different genesis. S. centauroides in the dose of 150 mg/kg has the most pronounced antihypoxic activity, increasing the lifespan of the animals with hemic and normobaric hypoxia on average by 60 % (p < 0,001) and and with histotoxic hypoxia - by 50 % (p < 0,001).